APPLICATION OF METHODS FOR DEVELOPING COGNITIVE COMPETENCES OF PRIMARY STUDENTS (Academicia Globe: Inderscience Research, 2025)
This article analyzes the directions of development of cognitive competencies of primary school students. Cognitive competence is the process of formation of students' skills of information reception, processing, logical analysis, problem solving and independent thinking, which is one of the important factors in increasing the effectiveness of education. At the same time, pedagogical technologies such as problem-based learning, research methods, game methods, interactive methods, constructive approaches, visual methods and reflection were used, and their impact on the thinking process of students was studied. Also, cases of incorrect application of methods in mathematics lessons were analyzed, revealing how they can negatively affect the cognitive development of students. The results of the study can serve as a theoretical and practical basis for primary school teachers, pedagogues and educational methodologists.